Water conservancy projects in China: Achievements, challenges and way forward - Liu, Junguo; Zang, Chuanfu; Tian, Shiying; Yang, Hong; Jia, Shaofeng; You, Liangzhi; Liu, Bo; Zhang, Miao (Elsevier, 2013)
China's water policies in the past decades have relied heavily on the construction of massive water conservancy projects in the form of dams and reservoirs, water transfer projects, and irrigation infrastructure. These facilities have brought tremendous economic and social benefits but also posed many adverse impacts on the eco-environment and society. With the intensification of water scarcity, China's future water conservancy development is facing tremendous challenge of supporting the continuous economic development while protecting the water resources and the dependent ecosystems. This paper provides an overview of China's water conservancy development, and illustrates the socioeconomic, environmental and ecological impacts. A narrative of attitude changes of the central government towards water conservancy, as well as key measures since the 1950s is presented. The strategic water resources management plan set by the central government in its Document No. 1 of 2011 is elaborated with focus on the three stringent controlling "redlines" concerning national water use, water use efficiency and water pollution and the huge investments poised to finance their implementation. We emphasize that realizing the goals set in the strategic plan requires paradigm shifts of the water conservancy development towards maximizing economic and natural capitals, prioritizing investment to preserve intact ecosystems and to restore degraded ecosystems, adapting climate change, balancing construction of new water projects and rejuvenation of existing projects, and managing both "blue" (surface/groundwater) and "green" water (soil water).